A chromosome conformation capture ordered sequence of the barley genome - Mascher, Martin; Gundlach, Heidrun; Himmelbach, Axel; Beier, Sebastian; Twardziok, Sven O.; Wicker, Thomas; Radchuk, Volodymyr; Dockter, Christoph; Hedley, Pete E.; Russell, Joanne; Bayer, Micha; Ramsay, Luke; et al. (Nature (London), 2017)
Cereal grasses of the Triticeae tribe have been the major food source in temperate regions since the dawn of agriculture. Their large genomes are characterized by a high content of repetitive elements and large pericentromeric regions that are virtually devoid of meiotic recombination. Here we present a high-quality reference genome assembly for barley ( Hordeum vulgare L.). We use chromosome conformation capture mapping to derive the linear order of sequences across the pericentromeric space and to investigate the spatial organization of chromatin in the nucleus at megabase resolution. The composition of genes and repetitive elements differs between distal and proximal regions. Gene family analyses reveal lineage-specific duplications of genes involved in the transport of nutrients to developing seeds and the mobilization of carbohydrates in grains. We demonstrate the importance of the barley reference sequence for breeding by inspecting the genomic partitioning of sequence variation in modern elite germplasm, highlighting regions vulnerable to genetic erosion. The International Barley Genome Sequencing Consortium reports sequencing and assembly of a reference genome for barley, Hordeum vulgare . Barley genome sequenced Triticeae grasses, which include barley, wheat and rye, are widely cultivated plants with particularly complex genomes and evolutionary histories. Sequencing of the barley genome has been particularly challenging owing to its large size and particular genomic features, such as an abundance of repetitive elements. Nils Stein and colleagues of the International Barley Genome Sequencing Consortium report sequencing and assembly of a reference genome for barley ( Hordeumvulgare L). They use a combined approach of hierarchical shotgun sequencing of bacterial artificial chromosomes, genome mapping on nanochannel arrays and chromosome-scale scaffolding with Hi-C sequencing. This brings the first comprehensive, completely ordered assembly of the pericentromeric regions of a Triticeae genome. The authors also sequenced and examined genetic diversity in the exomes of 96 European elite barley lines with a spring or winter growth habit, and highlight the utility of this resource for cereal genomics and breeding programs.